The main factors of integration and integration trends (International relations and international law Journal, 2016)
Humanity has stepped over the threshold of the twenty-first century. The last two millennia have been an epoch of wars and revolutions, which are not brought to mankind nothing but strife, disease, destruction and division, both between nations and between nations and states. The new century and a new millennium must fundamentally change the relationship. The new century and a new millennium must be the era of integration of peoples, countries, continents, globalization of the economy and globalization in all spheres of human life, in order to avoid wars, revolutions and manifestations of racism and hatred between peoples. The main idea of this article is contained in the following thesis: “The twenty-first century – a century of integration and globalization”.
Keywords: integration; rapprochement nations; interconnected world